2022
DOI: 10.1111/pedi.13381
|View full text |Cite
|
Sign up to set email alerts
|

An effective and cost‐saving structured education program teaching dynamic glucose management strategies to a socio‐economically deprived cohort with type 1 diabetes in a VIRTUAL setting

Abstract: Objectives Compare the clinical and cost‐effectiveness of an established face to face (F2F) structured education program to a new remote (VIRTUAL) program teaching dynamic glucose management (DynamicGM) to children and young people with type 1 diabetes (CYPD) using continuous glucose monitoring (CGM). To ascertain the most effective DynamicGM strategies predicting time in range (TIR) (3.9–10.0 mmol/L) and incorporating these into a user‐friendly teaching aid. Design and methods Effectiveness of the F2F and VIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…This suggests using moderate activity to quickly treat hyperglycemia between meals may be a novel strategy worth exploring in clinical trials. In addition, for 100 youths, the implementation of the mnemonic “GAME,” Glucose time in range desired, Alert on high set accordingly, Mode of moderate‐intensity activity, Exercise on high alert between meals if possible for 10–40 min depending on glucose value and trend arrow, was the strongest predictor of time in range (3.9–10.0 mmol/L or 70–180 mg/dl) 6 months after attending structured education focused on pro‐active CGM management 131 . A strategy like this may offer parents and children another option to improve time in range by quickly lowering between‐meal hyperglycemia, provided the blood ketone level is not elevated.…”
Section: Integrating Insulin and Nutrition Strategies For Acute Exerc...mentioning
confidence: 99%
“…This suggests using moderate activity to quickly treat hyperglycemia between meals may be a novel strategy worth exploring in clinical trials. In addition, for 100 youths, the implementation of the mnemonic “GAME,” Glucose time in range desired, Alert on high set accordingly, Mode of moderate‐intensity activity, Exercise on high alert between meals if possible for 10–40 min depending on glucose value and trend arrow, was the strongest predictor of time in range (3.9–10.0 mmol/L or 70–180 mg/dl) 6 months after attending structured education focused on pro‐active CGM management 131 . A strategy like this may offer parents and children another option to improve time in range by quickly lowering between‐meal hyperglycemia, provided the blood ketone level is not elevated.…”
Section: Integrating Insulin and Nutrition Strategies For Acute Exerc...mentioning
confidence: 99%
“…Study Population. CYPD attending the "CGM Academy" from April 2019 to January 2022 at our centre [14]. All CYPD at Birmingham Children's Hospital who were initiated on CGM as per the National Institute for Health and Care Excellence (NICE) [15] criteria attended the CGM academy.…”
Section: Methodsmentioning
confidence: 99%
“…At our tertiary centre, as part of our continuous glucose monitoring (CGM) structured education programme, the "CGM Academy" initiated in 2019, we have taught the use of 10-15 min moderate activity between meals to lower blood glucose by ∼2.0 mmol/L [13,14]. We have previously reported the effectiveness of our structured education programme (n = 100) and demonstrated that using short bursts of activity to lower hyperglycaemia between meals is one of the strongest predictors of improved TIR [14]. In the current report, we aimed to further evaluate the specific relationship between the level of activity used and its effect on lowering hyperglycaemia and the risk of hypoglycaemia in the CGM academy cohort.…”
Section: Introductionmentioning
confidence: 99%
“… 23 24 We have successfully implemented this model in our CGM academy. 6 Inspired by this, we developed a similar virtual flipped learning programme catering for each AID system and evaluated its efficacy.…”
Section: Introductionmentioning
confidence: 99%